2017
DOI: 10.1093/abbs/gmx047
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TUG1 influences papillary thyroid cancer cell proliferation, migration and EMT formation through targeting miR-145

Abstract: LncRNA TUG1, a tumor oncogene associated with various human cancers, has been reported to be involved in regulating various cellular processes, such as proliferation, apoptosis and invasion through targeting multiple genes. However, its biological function in thyroid cancer cells has not been elucidated. The aim of this study is to measure TUG1 expression level and evaluate its function in thyroid cancer cells. LncRNA TUG1 expression levels in thyroid cancer tissues and three thyroid cancer cell lines (the ATC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 25 publications
2
129
0
Order By: Relevance
“…For instance, lncRNA TUG1 contributes to the progression of PTC by regulating miR‐145 . Another lncRNA called ABHD11‐AS1 was dramatically upregulated in PTC cells and promoted tumorigenesis via modulating BHD11‐AS1/miR‐199a‐5p/SLC1A5 axis . In addition, lncRNA myocardial infarction‐associated transcript (MIAT) was also highly expressed in PTC cells and enhanced tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lncRNA TUG1 contributes to the progression of PTC by regulating miR‐145 . Another lncRNA called ABHD11‐AS1 was dramatically upregulated in PTC cells and promoted tumorigenesis via modulating BHD11‐AS1/miR‐199a‐5p/SLC1A5 axis . In addition, lncRNA myocardial infarction‐associated transcript (MIAT) was also highly expressed in PTC cells and enhanced tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…As well as in the research of Liu et al () which displays a correlation between lncRNA H19, miR‐17‐5p, and YES1 in thyroid cancer as well as in Li, Shen, Li, Zhang, and Jin ()'s research which revealed the correlation between lncRNA n340790 and miR‐1254 in carcinogenesis acceleration of thyroid cancer. LncRNA/miRNA has been found to related with Wnt/β‐Catenin signaling (Wang, Lu, Geng, Yang, & Shi, ) or EMT formation (Lei, Gao, & Xu, ) in thyroid cancer. Their effectiveness in the treatment of PTC could be compared and applied into clinical researches in the hope of better the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…H19 was reported to competitively bind to miR‐17‐5p to regulate YES1 expression in TC, resulting in the promotion of TC cell proliferation and invasion . TUG1 also contributed to the progression of TC by functioning as a ceRNA competitively sponging miR‐145 . Similarly, through sponging miR‐129‐5p, TNRC6C‐AS1 indirectly upregulated UNC5B expression, thus promoting TC development.…”
Section: Discussionmentioning
confidence: 99%